Patterns of healthcare seeking among people reporting chronic conditions in rural sub‐Saharan Africa: findings from a population‐based study in Burkina Faso. Issue 12 (14th October 2020) - Do, Stefanie; Lohmann, Julia; Brenner, Stephan; Koulidiati, Jean‐Louis; Souares, Aurelia; Kuunibe, Naasegnibe; Hamadou, Saidou; Hien, Hervé; Winkler, Volker; De Allegri, Manuela
Abstract: Objective: Non‐communicable diseases are rapidly becoming one of the leading causes of morbidity and mortality in sub‐Saharan Africa. Yet, little is known about patterns of healthcare seeking among people with chronic conditions in these settings. We aimed to explore determinants of healthcare seeking among people who reported at least one chronic condition in rural Burkina Faso. Methods: Data were drawn from a cross‐sectional population‐based survey conducted across 24 districts on 52 562 individuals from March to June 2017. We used multinomial logistic regression to assess factors associated with seeking care at a formal provider (facility‐based care) or at an informal provider (home and traditional treatment) compared to no care. Results: 1124 individuals (2% of all respondents) reported at least one chronic condition. Among those, 22.8% reported formal care use, 10.6% informal care use, and 66.6% no care. The presence of other household members reporting a chronic condition (RRR = 0.57, 95%‐CI [0.39, 0.82]) was negatively associated with seeking formal care. Wealthier households (RRR = 2.14, 95%‐CI [1.26, 3.64]), perceived illness severity (RRR = 3.23, 95%‐CI [2.22, 4.70]) and suffering from major chronic conditions (RRR = 1.54, 95%‐CI [1.13, 2.11]) were positively associated with seeking formal care. Conclusion: Only a minority of individuals with chronic conditions sought formal care, with important differences due to socio‐economic status. Policies and interventions aimed at increasing the availability and affordability of services for early detection and management in peripheral settings should be prioritised. Abstract : Objectif: Les maladies non transmissibles deviennent rapidement l'une des principales causes de morbidité et de mortalité en Afrique subsaharienne. Pourtant, on en sait peu sur les profils de recherche de soins de santé chez les personnes atteintes de maladies chroniques dans ces milieux. Nous visions à explorer les déterminants de la recherche de soins de santé chez les personnes qui ont déclaré au moins une maladie chronique dans les régions rurales du Burkina Faso. Méthodes: Les données ont été tirées d'une enquête transversale de population menée dans 24 districts auprès de 52.562 personnes de mars à juin 2017. Nous avons utilisé une régression logistique multinomiale pour évaluer les facteurs associés à la recherche de soins chez un prestataire formels (soins en établissement) ou chez un prestataire informel (traitement à domicile et traditionnel) par rapport à l'absence de soins. Résultats: 1.124 personnes (2% de tous les répondants) ont déclaré au moins une maladie chronique. Parmi ceux‐ci, 22, 8% ont déclaré avoir recours à des soins formels, 10, 6% à des soins informels et 66, 6% à aucun soin. La présence d'autres membres du ménage déclarant une maladie chronique (RRR = 0, 57, IC95%: 0, 39, 0, 82) était associée négativement à la recherche de soins formels. Les ménages plus riches (RRR = 2, 14; IC95%: 1, 26–3, 64), la sévérité perçue de la maladie (RRR = 3, 23 ; IC95%: 2, 22–4, 70) et souffrir de maladies chroniques majeures (RRR = 1, 54 ; IC95%: 1, 13–2, 11) étaient positivement associés à la recherche de soins formels. Conclusion: Seule une minorité de personnes atteintes de maladies chroniques ont recherché des soins formels, avec des différences importantes en raison du statut socioéconomique. Les politiques et interventions visant à accroître la disponibilité et l'accessibilité des services de détection précoce et de prise en charge dans les régions périphériques doivent être prioritaires.